2007
DOI: 10.1086/512725
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopy of SMC Wolf-Rayet Stars Suggests that Wind Clumping Does Not Depend on Ambient Metallicity

Abstract: The mass-loss rates of hot, massive, luminous stars are considered a decisive parameter in shaping the evolutionary tracks of such stars and influencing the interstellar medium on galactic scales. The small-scale structures (clumps) that are omnipresent in such winds may reduce empirical estimates of mass-loss rates by an evolutionarily significant factor of ≥3. So far, there has been no direct observational evidence that wind clumping may persist at the same level in environments with a low ambient metallicit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 27 publications
1
13
0
Order By: Relevance
“…We have demonstrated that the clumping factor is nearly the same in LMC and SMC as in our Galaxy. This agrees with observational studies that also found that the level of clumping does not depend on metallicity (Marchenko et al 2007, Mokiem et al 2007b). The observational dependence of mass-loss rate on luminosity in Fig.…”
Section: Calculated Global Wind Modelssupporting
confidence: 92%
“…We have demonstrated that the clumping factor is nearly the same in LMC and SMC as in our Galaxy. This agrees with observational studies that also found that the level of clumping does not depend on metallicity (Marchenko et al 2007, Mokiem et al 2007b). The observational dependence of mass-loss rate on luminosity in Fig.…”
Section: Calculated Global Wind Modelssupporting
confidence: 92%
“…Studies confirm that massive star winds are also clumped at low metallicities (Marchenko et al 2007). This implies that empirically derived mass-loss rates corrected for clumping would be lower than those obtained using the standard recipe.…”
Section: Metallicity Clumping and Mass-loss Ratementioning
confidence: 91%
“…be slightly stronger than in our models. Marchenko et al (2007) concluded that there is no metallicity dependence of the clumping properties but their conclusion is based on a small sample of Wolf-Rayet stars. In addition these objects have winds that do not behave exactly as those of OB stars (e.g., Sander et al 2017).…”
Section: Metallicity Of the Small Magellanic Cloudmentioning
confidence: 98%